Is democracy exportable? - Barany, Zoltan D.; Moser, Robert G., 1966- (Cambridge University Press, 2009)
Can democratic states transplant the seeds of democracy into developing countries? What have political thinkers going back to the Greek city-states thought about their capacity to promote democracy? How can democracy be established in divided societies? This books answers these and other fundamental questions.